Meta-Analysis for the Global Prevalence of Foodborne Pathogens Exhibiting Antibiotic Resistance and Biofilm Formation - Tao, Qian; Wu, Qian; Zhang, Zhaohuan; Liu, Jing; Tian, Cuifang; Huang, Zhenhua; Malakar, Pradeep K.; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2022)
Antibiotic-resistant (AMR) foodborne bacteria causing bacterial infections pose a serious threat to human health. In addition, the ability of some of these bacteria to form biofilms increases the threat level as treatment options may become compromised. The extent of antibiotic resistance and biofilm formation among foodborne pathogens remain uncertain globally due to the lack of systematic reviews. We performed a meta-analysis on the global prevalence of foodborne pathogens exhibiting antibiotic resistance and biofilm formation using the methodology of a Cochrane review by accessing data from the China National Knowledge Infrastructure (CNKI), PubMed and Web of Science databases between 2010 to 2020. A random effects model of dichotomous variables consisting of antibiotic class, sample source, and foodborne pathogens was completed using data from 332 studies in 36 countries. The results indicated AMR foodborne pathogens has become a worrisome global issue. The prevalence of AMR foodborne pathogens in food samples was greater than 10% and these foodborne pathogens were most resistant to β-lactamase antibiotics with Bacillus cereus being most resistant (94%). The prevalence of AMR foodborne pathogens in human clinical specimens was greater than 19% and the resistance of these pathogens to the antibiotic class used in this research were higher. Independently, the overall biofilm formation rate of foodborne pathogenic bacteria was 90% (95%CI, 68%-96%) and a direct linear relationship between biofilm formation ability and antibiotic resistance was not established. Future investigations should document both AMR and biofilm formation of the foodborne pathogen isolated in samples. The additional information could lead to alternative strategies to reduce the burden cause by AMR foodborne pathogens.